Analisis Organizational Culture dan Communication Terhadap Employee Engagement Melalui Job Satisfaction Pada Karyawan Bank Swasta di Jawa Tengah - Dhevi Dadi Kusumaningtyas; Pindo Asti; Yosefa Maria Seran; Endang Kustami; Tri Imaliya (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This study investigates the influence of work satisfaction, organizational culture, and communication on employee engagement within private banks in Central Java. The study's population comprised 150 private bank employees in Central Java, categorized as millennials aged 27 to 41, representing the most significant workforce demographic. Utilizing a non-probability sampling strategy through purposive sampling methodology. Data gathering uses a questionnaire method, with each item evaluated using a Likert scale. The study employed the SEM-PLS technique for data analysis, utilizing the SmartPLS 4.1.0.3 tool for data processing. The research findings indicate that communication positively and significantly influences employee engagement and job satisfaction, while organizational culture also positively and significantly affects both employee engagement and job satisfaction. The mediation test revealed that job satisfaction does not mediate substantially the connection between organizational culture and communication about employee engagement in private banks in Central Java.